The role of common dyadic coping as mediator between attachment styles and marital satisfaction in transition to parenthood - Kuswanto, Mahira Syafana; Ginanjar, Adriana Soekandar; Belinda Rumondor, Pingkan Cynthia (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
In the transition to parenthood, couples will face many changes until the child is two years old. Therefore, it is important for couples to apply common dyadic coping. However, common dyadic coping is influenced by individual attachment styles. This study aimed to determine the role of common dyadic coping during the transition to parenthood as a mediator between attachment style and marital satisfaction. This study uses a type of correlational research because correlational research is used to see the predictive relationship between variables. The measures used in this study are Experiences in Close Relationships - Revised (ECR-R), Couple Satisfaction Index (CSI), and Dyadic Coping Inventory (DCI). Data were obtained through an online survey of Indonesian citizens aged ≥ 21 years, married, and having an only child aged zero to two years (N mothers = 90%, M age = 27.9, SD age = 2.8). The results of the mediation model analysis on Hayes' PROCESS macro showed that problem-focused common dyadic coping partially mediated the relationships between anxious attachment and marital satisfaction, and avoidant attachment and marital satisfaction. Similarly, emotion-focused dyadic coping partially mediated the relationships between anxious attachment and marital satisfaction, and avoidant attachment and marital satisfaction.